Accuracy of Mobile Phone and Handheld Light Microscopy for the Diagnosis of Schistosomiasis and Intestinal Protozoa Infections in Côte d'Ivoire. - Jean T Coulibaly; Mamadou Ouattara; Michael V D'Ambrosio; Daniel A Fletcher; Jennifer Keiser; Jürg Utzinger; Eliézer K N'Goran; Jason R Andrews; Isaac I Bogoch (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Handheld light microscopy using compact optics and mobile phones may improve the quality of health care in resource-constrained settings by enabling access to prompt and accurate diagnosis. METHODOLOGY:Laboratory technicians were trained to operate two handheld diagnostic devices (Newton Nm1 microscope and a clip-on version of the mobile phone-based CellScope). The accuracy of these devices was compared to conventional light microscopy for the diagnosis of Schistosoma haematobium, S. mansoni, and intestinal protozoa infection in a community-based survey in rural Côte d'Ivoire. One slide of 10 ml filtered urine and a single Kato-Katz thick smear from 226 individuals were subjected to the Newton Nm1 microscope and CellScope for detection of Schistosoma eggs and compared to conventional microscopy. Additionally, 121 sodium acetate-acetic acid-formalin (SAF)-fixed stool samples were examined by the Newton Nm1 microscope and compared to conventional microscopy for the diagnosis of intestinal protozoa. PRINCIPAL FINDINGS:The prevalence of S. haematobium, S. mansoni, Giardia intestinalis, and Entamoeba histolytica/E. dispar, as determined by conventional microscopy, was 39.8%, 5.3%, 20.7%, and 4.9%, respectively. The Newton Nm1 microscope had diagnostic sensitivities for S. mansoni and S. haematobium infection of 91.7% (95% confidence interval (CI) 59.8-99.6%) and 81.1% (95% CI 71.2-88.3%), respectively, and specificities of 99.5% (95% CI 97.0-100%) and 97.1% (95% CI 92.2-99.1%), respectively. The CellScope demonstrated sensitivities for S. mansoni and S. haematobium of 50.0% (95% CI 25.4-74.6%) and 35.6% (95% CI 25.9-46.4%), respectively, and specificities of 99.5% (95% CI 97.0-100%) and 100% (95% CI 86.7-100%), respectively. For G. intestinalis and E. histolytica/E. dispar, the Newton Nm1 microscope had sensitivity of 84.0% (95% CI 63.1-94.7%) and 83.3% (95% CI 36.5-99.1%), respectively, and 100% specificity. CONCLUSIONS/SIGNIFICANCE:Handheld diagnostic devices can be employed in community-based surveys in resource-constrained settings after minimal training of laboratory technicians to diagnose intestinal parasites.